Anti-diabetic Activity of Virgin Coconut Oil (VCO): Review - Rahmawati Rahmawati; Bayu Putra; Lastri Wiyani; Andi Maulana Kamri; Sitti Azahra (Journal Borneo, 2023)
Diabetes mellitus is a metabolic disease characterized by increased blood glucose levels. Currently, the treatment of diabetes mellitus uses synthetic or chemical drugs and natural ingredients such as virgin coconut oil. Virgin coconut oil (VCO) is extracted with minimal heating and no chemical purification process. This study aims to obtain data on the impact of VCO as an antidiabetic obtained from several research journals. This literature study uses a narrative review method obtained from the Google Scholar, Pubmed, and Science Direct databases. The results of this study indicate that VCO can be used as an alternative to lowering blood glucose levels because it has antidiabetic activity. Medium-chain fatty acid (MCFA) lauric acid in VCO can stimulate insulin production in pancreatic beta cells. This study concludes that virgin coconut oil can potentially reduce blood sugar levels.